2015
DOI: 10.1007/s00477-015-1096-3
|View full text |Cite
|
Sign up to set email alerts
|

Functional outlier detection by a local depth with application to NO x levels

Abstract: This paper proposes methods to detect outliers in functional data sets and the task of identifying atypical curves is carried out using the recently proposed kernelized functional spatial depth (KFSD). KFSD is a local depth that can be used to order the curves of a sample from the most to the least central, and since outliers are usually among the least central curves, we present a probabilistic result which allows to select a threshold value for KFSD such that curves with depth values lower than the threshold… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 21 publications
1
27
0
Order By: Relevance
“…Hence, the bootstrap procedure can be called conservative. This finding is also supported by Sguera et al 19 Still, a few exceptions can be found for the h-modal depth; see (d). (c) When assuming Gaussian error and inverse or logistic link, regardless of the true error distribution, it turns out that MBD outperforms the other depths.…”
Section: Main Findingssupporting
confidence: 85%
See 3 more Smart Citations
“…Hence, the bootstrap procedure can be called conservative. This finding is also supported by Sguera et al 19 Still, a few exceptions can be found for the h-modal depth; see (d). (c) When assuming Gaussian error and inverse or logistic link, regardless of the true error distribution, it turns out that MBD outperforms the other depths.…”
Section: Main Findingssupporting
confidence: 85%
“…Thereby, we gain μ̂i(t)=hβ̂0(t)+j=1kxi,jβ̂j(t)=hη̂i(t),i=1,,n, as fitted observations and estimated deviance residuals trueϵ̂i(t)=sign(yi(t)trueμ̂i(t))di(t), where d i ( t ) denotes the contribution of the i th component to the deviance. Other residual types like Pearson or working residuals have certain drawbacks, see Wood, Chap. 2].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Febrero, Galeano, and Gonzalez-Manteiga (2007) and Shang (2015), a functional outlier is a curve generated by a stochastic process that has a different distribution from that of normal curves. This general definition covers many types of outliers: for example, magnitude, shape, and partial outliers (see Sguera, Galeano, & Lillo, (2016), for more details).…”
Section: Intraday Sandp 500 Indexmentioning
confidence: 99%